Development of Knowledge and Attitude Measurement Tools in Disaster Preparedness Schools - Setiawan, Theresita Herni; Salim, Gregorio Hernando; Wimala, Mia; Van Roy, Andreas Franskie; Adianto, Yohanes Liem Dwi (International Journal of Disaster Management, 2020)
Indonesia is the largest archipelago country in the world located at the confluence of four tectonic plates. This condition makes Indonesia potentially and become vulnerable to natural hazard that have a significant impact and reach various sectors. One of the impacts of natural hazard that occurred in Indonesia is the education sector. This natural hazard has an impact on the physical building of schools and also hinders the process of teaching and learning, causing trauma, and even fatalities at school. The Indonesian Institute of Sciences (LIPI) through the Community Preparedness (COMPRESS) program inaugurated disaster preparedness education at the school community level. In 2008, LIPI began implementing disaster risk reduction by developing a model of disaster preparedness schools. Then LIPI published Guidelines for Implementing Disaster Preparedness Schools in 2013. This guide does not yet have a specific Knowledge and Attitude category and can be used as a reference. Therefore, the development of the Disaster Preparedness School Implementation Manual needs to be done. The development of this measuring instrument was analysed by compiling a comparison matrix using the AHP method so as to produce a new development system from the Knowledge and Attitude assessment category. This study produced 3 sub-categories of Knowledge and Attitude assessment, namely (1) Standard Operating Procedure (SOP) for Teaching and Learning Disasters with a weight of 33%, (2) Knowledge about Disasters and Disaster Management with a weight of 43%, and (3) Knowledge Access About Disasters and Disaster Management with a weighting of 24%. Such approach can be used in advancement of others variables of measuring tool for school preparedness.